Nostalgia and impulse buying behavior : the mediator role of conspicuous consumption - Chua, Jia Zhen (2018)
The purpose of this research is to investigate the relationship between nostalgia, impulse buying and conspicuous consumption. Specifically, the study examines how nostalgia can affect impulse buying and conspicuous consumption in sports product consumers. A total of 315 participants were randomly recruited to participate in this study. They were asked to complete a survey questionnaire. Thereafter, the data collected were analyzed using Statistical Package for the Social Science (SPSS) and Analysis of Moment Structures (AMOS) software. The results show all hypotheses to be supported: (i) nostalgia significantly affects impulse buying, (ii) nostalgia significantly affects conspicuous consumption, (iii) conspicuous consumption significantly affects impulse buying, and (iv) conspicuous consumption significantly mediates an indirect effect between nostalgia and impulse buying. This research will aid sports product marketers to better understand the unique consumer behaviors of impulse buying and conspicuous consumption.